The Influence Of Work Ethic And Work Motivation On Employee Performance At The Pesawaran District Pamong Praja Police Unit - Selfiana, Yanita; Pradana , M. Rafieq Adi (Universitas Dehasen Bengkulu, 2025)
Organizations and employees are two things that need each other. If employees succeed in bringing progress to an agency, then the benefits will be obtained by both parties. For employees, success is the actualization of self-potential as well as an opportunity to fulfill their life needs. While for an agency, success is a means towards the growth and development of an agency. With a high work ethic, employees will be motivated to make a positive contribution to the progress of the organization, so that the goals expected by the organization can be achieved optimally. This research was conducted at the Civil Service Police Unit of Pesawaran Regency. This study aims to find the effect of work ethic and work motivation on employee performance at the Civil Service Police Unit of Pesawaran Regency. The type of research used in this study is a quantitative research model. This study used 34 research respondents.There are three variables in this study, namely 2 independent variables X1 and X2 and 1 dependent variable Y. Based on the results of data analysis, the answer to the hypothesis was found as follows; there is an influence of the work ethic variable (X1) on the employee performance variable (Y), with an influence level (R-square) of 49.2%. There is an influence of the work motivation variable (X2) on the employee performance variable (Y), with an influence level of 55.8%. There is an influence of the work ethic variable (X1) and the work motivation variable (X2) together on the employee performance variable (Y), with an influence level of 69.6%. Based on data analysis through hypothesis testing, both partially and simultaneously, it is stated that each independent variable has an influence on the dependent variable and there are things that need to be improved in order to improve employee performance in order to achieve organizational goals.